Supply Chain Management in Delivery of Goods to Increase Customer Loyalty in Electronic Commerce - Leonid Aleksandrovich Bragin; Svetlana Victorovna Panasenko; Alexander Fedorovich Nikishin; Tat'yana Viktorovna Pankina; Svetlana Borisovna Aleksina (International Journal of Supply Chain Management, 2020)
Abstract— Delivery performance provides an indication of how successful the supply chain is at providing products and services to the customer. In modern conditions, electronic commerce of supply chain is developing very dynamically. The significant increase in the level of competition in this sector due to this leads to the need to find new ways to attract and retain customers in supply chain system. In this regard, the relevance of the study related to finding criteria for the competitiveness of online stores is not in doubt. The paper discusses aspects concerning the formation of competitive advantages of online stores to gain customer loyalty and improve the quality of service. Such advantages are primarily associated with increased comfort for buyers along the entire path of making a purchase, starting with the search and accumulation of information about products and purchase conditions and ending with the receipt of goods. The authors have studied factors significant for customers to choose online stores, as well as the reasons for refusing online purchases. Buyers in the Internet commerce segment note among the main reasons for refusing a purchase the difficulties in returning goods purchased on the network and in solving problems arising during the purchase and delivery of an order; they also express concern about the quality of the goods, and also note problems with the delivery of goods. As a result of the study, it was found that the factors of convenience of making an order, as well as the convenience of receiving a purchase, are priority, while the price factor has somewhat lost its significance. When choosing an online store, a significant number of buyers study the conditions for the delivery of goods and make purchase decisions based on supply chain process. At the same time, it becomes essential for buyers to customize the delivery parameters to suit their needs.